Relevance of Cor Pulmonale in COPD With and Without Pulmonary Hypertension: A Retrospective Cohort Study - Yogeswaran, Athiththan; Kuhnert, Stefan; Gall, Henning; Faber, Marlene; Krauss, Ekaterina; Rako, Zvonimir A.; Keranov, Stanislav; Grimminger, Friedrich; Ghofrani, Hossein Ardeschir; Naeije, Robert; Seeger, Werner; Richter, Manuel J.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The relevance of cor pulmonale in COPD and pulmonary hypertension due to COPD (PH-COPD) is incompletely understood. We aimed to investigate the relationship of right ventricular-pulmonary arterial (RV-PA) uncoupling with disease severity in COPD, and the relationship of RV-PA uncoupling and use of targeted PH therapies with mortality in PH-COPD. Methods We retrospectively analyzed 231 patients with COPD without PH and 274 patients with PH-COPD. COPD was classified according to GOLD stages and the modified Medical Research Council dyspnoea scale. PH was categorized as mild-to-moderate or severe. RV-PA uncoupling was assessed as the echocardiographic tricuspid annular plane systolic excursion/pulmonary artery systolic pressure (TAPSE/PASP) ratio. Results Of the cohort with COPD without PH, 21, 58, 54 and 92 were classified as GOLD I, II, III and IV, respectively. Patients in advanced GOLD stages and those with severe dyspnoea showed significantly decreased TAPSE/PASP. Of the PH-COPD cohort, 144 had mild-to-moderate PH and 130 had severe PH. During follow-up, 126 patients died. In univariate Cox regression, TAPSE/PASP and 6-min walk distance (6MWD; 10 m increments) predicted survival [hazard ratios (95% CI): 0.12 (0.03–0.57) and 0.95 (0.93–0.97), respectively]; notably, PH severity and simplified European Society of Cardiology/European Respiratory Society risk stratification did not. Among patients in the lowest or intermediate tertiles of TAPSE/PASP and 6MWD, those with targeted PH therapy had higher survival than those without (53 vs. 17% at 3 years). Conclusion Cor pulmonale (decreased TAPSE/PASP and 6MWD) is associated with disease severity in COPD and predicts outcome in PH-COPD.